Design Of Safety Features For Heavy Vehicles In Malaysia - Md Yusof, Hasrul Izatie (2018)
Often reported in newspaper or other mass media about accidents involving heavy vehicles in Malaysia.Hence,the safety features are capable to avoid unexpected things happen such as accident in particular.So,the design for safety features will be discussed where some of the existing safety features will be reviewed and improved. Besides,the performance of heavy vehicles to carry loads when climbing the hill also will be analysed.The methodology for this project consists of survey,analysis, calculation,and simulation.The survey is to investigate the use of current active safety as the warning signal which are lights,light reflection stickers,and the colour of canvas used on heavy vehicles.Therefore,the safety features that need to be emphasized in redesign or recommend change is light reflection stickers.This is because light reflection stickers can be an additional source of lights besides the lamp on heavy vehicles. Although the lights on heavy vehicles in not sufficient, light reflection stickers can be an aid to light the heavy vehicles.As for the canvas used,it is insignificant since the canvas is slightly up above the view of human eyes so this is no need to redesign in urgent.The speed required for the heavy vehicles to climb the hill with certain load have been identified where these required speed can be a guide to the driver where they need to drive exceeded those speed to pass the hill smoothly. Other road users also will move up the hill smoothly without the presence of heavy vehicles stranded at the hills and the usual congestion caused by heavy vehicles also can be reduced.In addition the simulation on the impact analysis also have been made by using ABAQUS where the collision between car and heavy vehicle can be seen. This is also to simulate the use of safety speed between cars and heavy vehicles.Hence,the conclusion can be made as the slower the speed the higher the stress faced by the car’s bumper and its condition will become worse. Besides,the heavier the heavy vehicles the slower it’s moving and the more dangerous it could be to the other road users.